Predictors of poor reading performance in student-athletes following sport-related concussion. Issue 3 (3rd July 2022) - Sherry, Natalie; Trbovich, Alicia; Holland, Cyndi; Eagle, Shawn; Bitzer, Hannah; Kontos, Anthony P.
Abstract: The goal of the current study was to determine which sport/recreation-related concussion (SRC) assessments predict academic reading performance following SRC. The study included 70 concussed students aged 14–22 years ( M  = 16.21, SD  = 1.90) evaluated 2–30 days ( M  = 8.41, SD  = 5.88) post-injury. SRC assessments included: Post-Concussion Symptom Scale, Immediate Post-Concussion Assessment and Cognitive Testing, Vestibular/Ocular Motor Screening, and King-Devick test. The Nelson-Denny Reading Test (NDRT) comprehension subtest measured academic reading accuracy and rate. Pearson correlations examined relationships among SRC assessments and reading accuracy/rate; those assessments that significantly correlated with the NDRT were included in multiple regressions (MRs) predicting reading accuracy and reading rate. Results supported positive correlations between visual motor speed and reading accuracy ( r  = .31, p  = .01), and near point of convergence (NPC) and reading rate ( r  = .30, p  = .01). The MRs for reading accuracy ( F  = 4.61, p  = .01) and reading rate ( F  = 4.61, p  = .01) were significant, and predicted approximately 40% of the variance, with visual motor speed and NPC as the only significant predictors in both models. Symptoms were not predictive of reading accuracy or rate. The present study indicates that visual motor speed and NPC are predictive of academic reading performance after SRC, suggesting clinicians should consider these clinical outcomes to better inform academic accommodations.